The Influence of Job Stress, Job Satisfaction and Work Environment On Organizational Commitment of Keluarga Sehat Clinic Wedoro Sidoarjo - Diana, Safitri Nur; Putra, Bayu Airlangga; Arif, Mochammad (Yayasan Ahmar Cendekia Indonesia, 2020)
This study aims to determine the effect of work stress, job satisfaction and work environment on keluarga sehat clinic wedoro sidoarjo. This type of research is quantitative, where researchers distribute questionnaires as a medium for data collection and then processed into interval data which is then processed using SPSS18. The population and sample of this study are 36 employees of keluarga sehat clinic wedoro sidoarjo. Hypothesis test results partially work stress partially negative and significant effect on organizational commitment, job satisfaction partially has a positive and significant effect on organizational commitment, and work environment partially does not significantly influence organizational commitment. And the results of the simultaneous hypothesis test was calculated to be 11.570 and included to be greater than Ftable = 2.92. This means that H0 is rejected and H1 is accepted and the significant value is 0,000 less than 0.05. So job stress, job satisfaction and work environment simultaneously have a significant effect on organizational commitment. While the determination test obtained by the coefficient R Square 0.5202 means that the relationship between job stress, job satisfaction and work environment on organizational commitment has an effect of 52.0%, while the remaining 48.0% is explained by other variables not included in the modeling.